Cooperação e governança nos arranjos produtivos locais: estudo de caso nas empresas de software no estado do Paraná - Gussoni, Wendell Myler da Silva (2013)
Local Productive Arrangements (APLs) have become an important instrument of competitiveness and local development. The cooperation between economic agents of these clusters is the need for coordination of resources and information, and these are also the governance structure that deals with formal institutions and regimes of coordination and authority and informal systems. This research is aimed to APLs, and aims to analyze how cooperation and governance contribute to the improvement of organizational performance of companies operating in Local Productive Software Paraná. Therefore, we used an exploratory descriptive qualitative and quantitative approach. The results showed that the forms of cooperation shown by respondents from 40 companies participated in the survey, contribute to organizational performance. It was also found that governance has contributed to the growth of these arrangements, as these clusters has been developed on a competitive basis, increasingly strengthened cooperation between entrepreneurs, and this is only possible with a good governance structure.